Microgrid Energy Management System - Manur, Ashray Gururaja (My University, 2015)
The concept of microgrid is emerging to be a viable approach to integrate various types of electricity sources and storage devices within or close to load locations. While the fundamental technical features of microgrids have been demonstrated in laboratory and field settings, a large number of operational issues remain to be solved before they can become widespread. Chief among them is an approach for asset or energy management within the microgrid. In contrast to the well-established centralized electricity grid enterprise, microgrids are expected to be small in scale and maintain a peer-to-peer interaction among devices with rough parity between supply and demand in terms of size. In this scenario, it is critical to have a robust operational protocol within the microgrid to prioritize and manage loads, sources and storage to prevent the collapse of the microgrid. This study presents the design framework for a Microgrid Energy Manager (MEM) which uses the internet of things (IoT) paradigm and wireless sensor networks (WSN) to overlay a communication and control layer for real-time energy management in microgrids.